2015
DOI: 10.1099/vir.0.066555-0
|View full text |Cite
|
Sign up to set email alerts
|

Human respiratory syncytial virus infection is inhibited by IFN-induced transmembrane proteins

Abstract: The IFN immune system plays an essential role in protecting the host against most viral infections. In order to explore the interactions between the IFN pathway and human respiratory syncytial virus (RSV) infection, and to identify potential IFN-stimulated genes (ISGs) that may be involved in suppressing the replication of RSV, we utilized an IFN pathway-specific microarray to study the effects of RSV infection on the IFN pathway in HeLa cells. We showed that RSV infection enhanced the expression of a series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…Based primarily on studies in cell culture, the ISG IFITM3 has been suggested to have antiviral activity against a variety of viral pathogens, including flaviviruses (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). A demonstrable antiviral role for IFITM3/Ifitm3 in vivo has been established previously only for IAV and RSV (3,43,45,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based primarily on studies in cell culture, the ISG IFITM3 has been suggested to have antiviral activity against a variety of viral pathogens, including flaviviruses (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). A demonstrable antiviral role for IFITM3/Ifitm3 in vivo has been established previously only for IAV and RSV (3,43,45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Although initial studies described possible roles of IFITM1, IFITM2, and IFITM3 in development, apoptosis, cell proliferation, and cell signaling (5)(6)(7)(8)(9)(10)(11)(12)(13), a subsequent report suggested that ectopic expression of IFITM1 in mouse L cells could restrict infection of vesicular stomatitis virus (VSV) (14). A decade later, gene silencing and ectopic expression studies established that IFITM proteins have antiviral activity in cell culture against members of the Flaviviridae, Orthomyxoviridae, Filoviridae, Rhabdoviridae, Retroviridae, Bunyaviridae, Reoviridae, Togaviridae, and Paramyxoviridae families (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Nonetheless, some enveloped and nonenveloped viruses appear to be resistant to the actions of IFITM proteins, including arenaviruses, papillomaviruses, cytomegaloviruses, and adenoviruses (16,17,29).…”
mentioning
confidence: 99%
“…With RSV, similar modest inhibition was found with IRF2, IRF7, MAP3K14, HPSE, and THBD, and surprisingly, with cGAS, a DNA sensor. Four ISG proteins, namely, viperin (82), OASL (85), IFITM1 and IFITM3 (86), specifically shown to inhibit RSV in directed studies, were not found to be inhibitory in the screen. The apparent differences could be due to a number of reasons, such as differences in cell lines, expression levels of the ISG proteins, viral load, and assay methods.…”
Section: Discussionmentioning
confidence: 99%
“…We attempted de novo assembly of Illumina MiSeq paired-end reads using three software packages (namely IVA, SGA and HGAP) resulting in only partial consensus sequence covering between 50 and 70% of the full chIFITM locus (including the flanking genes ATHL1 and B4GALNT4) (data not shown). The best assembly was generated using IVA, which produced the least number of contigs (13). In order to identify Illumina contigs that contained the BAC, and specifically the chIFITM locus, sequence similarity was used to compare the Illumina MiSeq contigs with the PacBio contig 2 (Additional file 4).…”
Section: De Novo Assembly Of Pacbio and Miseq Sequencing Readsmentioning
confidence: 99%
“…Interferon inducible transmembrane (IFITM) proteins are effectors of the immune system widely involved in restricting entry into cells of a broad range of viruses including Influenza viruses, Ebola and Zika [8][9][10][11][12][13][14]. In chickens, four IFITM genes have been annotated to date by the chicken gene nomenclature consortium (CGNC), namely chIFITM1 (LOC422993-3-like), chI-FITM3 (LOC770612-1-like), chIFITM5, and chIFITM10 [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%